Business Cycles and Fertility The Impact of Unemployment on the Fertility Rate - Tománková, Ivana; Lahvička, Jiří, 1975-; Bartoň, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
This paper investigates how aggregate fertility responds to business cycle fluctuations and attempts to quantify this effect. The results of a first differences regression analysis on a 2003 to 2010 panel data sample of 31 member states of the Organization for Economic Co-operation and Development indicate procyclical fertility behavior over the business cycle. Ceteris paribus, a one percentage point increase in the general unemployment rate decreases the crude birth rate by 0.054. Tertiary educational attainment of the labor force, the average wage, the female-to-male wage ratio and the marriage and divorce rates are all positively related to fertility, while the employment rate of women exerts a fertility-depressing effect.
Vedoucí práce: Jiří Lahvička
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses